1993
DOI: 10.1128/aac.37.3.398
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin, rifabutin, and rifapentine for treatment and prophylaxis of Mycobacterium avium complex in rats treated with cyclosporine

Abstract: Azithromycin, rifabutin, and rifapentine were used to treat or prevent disseminated Mycobacterium avium complex (MAC) infections produced in rats immunosuppressed with cyclosporine. Animals with bacteremic infections were treated 1 week after intravenous inoculation with 107 CFU of MAC with azithromycin, 100 mg/kg of body weight administered subcutaneously for 5 days and then 75 mg/kg on Monday, Wednesday, and Friday, or with rifabutin or rifapentine, 20 mg/kg administered intraperitoneally on Monday through F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 24 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…Azithromycin is poorly soluble in water and thus requires the use of a cosolvent for subcutaneous administration (4). One cosolvent investigated is polyoxyethylated castor oil (Cremophor EL).…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is poorly soluble in water and thus requires the use of a cosolvent for subcutaneous administration (4). One cosolvent investigated is polyoxyethylated castor oil (Cremophor EL).…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin was selected because of the following properties: prolonged inhibition of the replication of intracellular tachyzoites (Chamberland, Kirst & Current, 1991); in-vitro activity against cyst forms (Huskinson-Mark, ; high tissue specificity, with concentrations in the brain which are almost ten-fold higher than those in serum after oral dosing (Araujo, Shepard & Remington, 1991); significant intracellular accumulation (Gladue el ai, 1989); and potent activity in experimental murine toxoplasmosis (Araujo, Guptill & Remington, 1988;Araujo et al, 1991;Derouin et al, 1992). A number of additional observations also suggested that azithromycin might be suitable in this context: a prolonged half-life (Girard et al, 1987), thereby allowing a simplified dosing schedule; good tolerability; lack of effect on zidovudine disposition in patients with AIDS (Chave et al, 1992); and potential activities against cryptosporidium and the Mycobacterium avium complex (Brown et al, 1993;Vargas et al, 1993). The 100-mg/kg/day dosage was used because it corresponds to that which is appropriate for man after size correction.…”
Section: Treated Animalsmentioning
confidence: 99%
“…Numerous studies have been performed either in vitro (25,28,36,49) or on macrophages (46) and in animal models (6,21,34,38,39) with classic or more recent antituberculous agents (ciprofloxacin, sparfloxacin, azithromycin, and clarithromycin) alone or in combi-…”
mentioning
confidence: 99%
“…For each type of tissue assay, an antibiotic calibration range was determined with the organ involved (6,45). The elimination half-life (t1/2/) was calculated according to a single-compartment model by exponential regression of the concentrations in serum from 0.25 to 2 h. Areas under the curve (AUCs) from 0 to 6 h were calculated by the trapezoidal rule method.…”
mentioning
confidence: 99%